Factors Influencing Birth Outcomes in Preeclampsia: A Descriptive Cross-sectional Study in Central India - Vaishali Soni; Shashi Prabha Tomar; Preeti Gupta; Sangeeta Devaliya (Archives of Medicine and Health Sciences)
Background and Aim: Preeclampsia significantly increases the risk of maternal and perinatal mortality. It is often undetected during pregnancy but can become fatal if not managed promptly. Lifestyle and dietary changes are recommended as a cost-effective approach to prevent pregnancy-induced hypertension. Therefore, the current study aims to investigate how dietary habits, physical activity, and antenatal care influence birth outcomes in mothers with preeclampsia. Materials and Methods: This cross-sectional study was conducted from August 2022 to January 2024 among 350 women who were admitted for delivery in a tertiary care hospital. Data collection was done by interview technique using a pretested self-structured questionnaire consisting of sociodemographic data, and information regarding antenatal period such as dietary habits, and physical activity. Results: Among 350 women, 68.85% were primigravida. The majority received inadequate antenatal care, leading to more adverse consequences during childbirth, with most newborns (71.18%) having low birth weight and premature delivery. 29.42% of women were unaware of their illness. Good compliance with iron-folic acid and calcium tablets showed positive effects, but dietary habits did not significantly impact birth outcomes. Moderate-to-heavy work was associated with lower rates of cesarean section. Conclusion: Preeclamptic mothers with good diets, physical activity, and adequate antenatal care have fewer adverse consequences compared to those with poor dietary practices and antenatal coverage. Despite existing health programs regarding mother and child health, there is a need to allocate resources toward enhancing nutritional services for pregnant women and more attractive packages for antenatal care.